Autophagy and Host Defense in Nontuberculous Mycobacterial Infection - Silwal, Prashanta; Kim, In Soo; Jo, Eun-Kyeong (Frontiers in Immunology, 2021)
Autophagy is critically involved in host defense pathways through targeting and elimination of numerous pathogens via autophagic machinery. Nontuberculous mycobacteria (NTMs) are ubiquitous microbes, have become increasingly prevalent, and emerging as clinically important strains due to drug-resistant issues. Compared to Mycobacterium tuberculosis (Mtb), the causal pathogen for human tuberculosis, it remains largely uncharacterized the roles of autophagy in the context of a variety of NTM infections. Compelling evidence suggests that host autophagy activation plays an essential role in the enhancement of antimicrobial immune responses and controlling pathological inflammation against various NTM infections. As similar to Mtb, it is believed that NTM bacteria evolve multiple strategies to manipulate and hijack host autophagy pathways. Despite this, it is just beginning to understand the molecular mechanisms underlying crosstalk between pathogen and host autophagy system in a battle with NTM bacteria. In this review, we will explore the function of autophagy which is involved in shaping host-pathogen interaction and disease outcomes during NTM infections. These efforts will lead to the development of autophagy-based host-directed therapeutics against NTM infection.